2015
DOI: 10.1617/s11527-015-0558-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of shear capacity of adhesive anchors for structures using neural network based model

Abstract: In this study, an artificial neural network (NN) based explicit formulation for predicting the edge breakout shear capacity of single adhesive anchors post-installed into concrete member was proposed. To this aim, a comprehensive experimental database of 98 specimens tested in shear was used to train and test NN model as well as to assess the accuracy of the existing equations given by American Concrete Institute and prestressed/precast concrete Institute. Moreover, the proposed NN model was compared with anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Pero un estudio de los efectos del estearato de calcio, el oleato de sodio y el metilsiliconato de sodio, aplicados a la absorción de agua, hidratación, resistencia a la compresión, fluidez y periodo de fraguado en la pasta de cemento, dio como resultado que el estearato de calcio es el elemento más adecuado para la preparación de concreto permeable ligero [35]. Al sustituir el agregado natural por AR resultó en un incremento considerable en el coeficiente de permeabilidad, pero las propiedades mecánicas del concreto se ven influenciadas adversamente [36].…”
Section: Introductionunclassified
“…Pero un estudio de los efectos del estearato de calcio, el oleato de sodio y el metilsiliconato de sodio, aplicados a la absorción de agua, hidratación, resistencia a la compresión, fluidez y periodo de fraguado en la pasta de cemento, dio como resultado que el estearato de calcio es el elemento más adecuado para la preparación de concreto permeable ligero [35]. Al sustituir el agregado natural por AR resultó en un incremento considerable en el coeficiente de permeabilidad, pero las propiedades mecánicas del concreto se ven influenciadas adversamente [36].…”
Section: Introductionunclassified
“…For anchors failing with a concrete cone failure, the mean value of the calculated to measured values for the testing dataset are 0.99 and 1.63 for the models based on ANN and the CCD method, respectively. A complementary study in [ 22 ] including an analysis by ANN on the same dataset, indicated that an ANN-based model delivered still a higher accuracy with correlation coefficients of 0.983 and 0.984 with the training and testing data, respectively. The fact that the correlation with both the testing and training data is virtually the same, allowed to conclude that the ANN has an overall more reliable prediction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Their destruction mechanism can cause extraordinary damage to a structure. In the last few years, much attention has been given to the use of artificial neural networks (ANNs) for solving various civil engineering problems [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%